Measuring and analyzing multidimensional relative poverty in Xinjiang from subjective and objective perspectives - Fengqin Wei; Xiaomeng Zhang (Discover Sustainability)
Abstract China has made significant progress in solving absolute poverty and has now entered a phase dedicated to addressing multidimensional relative poverty. Tackling multidimensional relative poverty is essential to facilitating social equity and achieving sustainable development. In this study, a Multidimensional Relative Poverty Index (MRPI) including both subjective and objective indicators was developed across three dimensions: economic, social, and environmental. The Alkire-Foster (AF) method was applied to assess the status of multidimensional relative poverty in Xinjiang using data from eight counties and cities. The results show that the multidimensional relative poverty incidence in Xinjiang is 5.73% (k = 15), with few households experiencing extreme multidimensional relative poverty. The environmental dimension is the largest contributor to MRPI (k = 10), accounting for 40.97%, while the economic dimension contributes the least at 20.83%. There are significant differences between objective and subjective indicator scores. In the economic and environmental dimensions, most objective indicators contribute significantly more than subjective ones. Conversely, in the social dimension, subjective indicators play a more substantial role. Therefore, future configurations of the MRPI should reasonably determine the indicators for the economic, social, and environmental dimensions while enhancing the incorporation of subjective indicators.